Calculate exact integrals in the visual basic window of excel - Nodira Sharifovna Khodjayeva; Muslimakhon Tokhirboyevna Yakhyayeva (Research Parks Publishing LLC, 2021)
A graphical view of the exact integral is shown and the execution is shown in the Visual basic window of Excel